Evaluating road safety interventions: prerequisites for a multi-country approach. (1st March 2011) - Hyder, A A; Trujillo, A; Bishai, D; Puvanachandra, P; Tran, N; Chandran, A; Ma, S; Stevens, K
Abstract : This workshop focuses on the global road safety interventions project in 10 countries supported by the Bloomberg Philanthropies. Key to the initiative is the demonstration that established interventions on road safety make a significant impact on public health. As a result, defining the epidemiology of road injuries, monitoring the implementation of programs, and assessing the impact of the programs in an objective and scientific manner will be critical for success. It is in this regard that three important functions have to be fulfilled: (1) defining baseline conditions: a prerequisite for demonstrating any change, a good baseline analysis of road traffic injuries in countries requires a multi-disciplinary review of multiple data sources and strengthening national data systems; (2) monitoring program rollout: continuous assessment of a program in terms of process indicators, and outputs to ensure that the operational elements were consistent with the planned program is needed to both identify challenges to implementation and ensure consistency; and (3) evaluating impact: overall assessment of the change in health, economic and social outcomes due to the implementation of road safety programs. This approach will have the strengths of: (1) development of a core set of methods for each function which are standardised across all road safety projects in all countries; (2) identification of a set of indicators which are scientifically valid and yet practical to measure at country-level for road safety evaluation; and (3) internal consistency across all elements of the evaluation while allowing for flexibility in country-specific approaches.